Sulfur Isotopic Fractionation of the Youngest Chang'e‐5 Basalts: Constraints on the Magma Degassing and Geochemical Features of the Mantle Source. Issue 15 (12th August 2022) - Liu, Xiaoying; Hao, Jialong; Li, Rui‐Ying; He, Yuyang; Tian, Heng‐Ci; Hu, Sen; Li, Jing; Gu, Lixin; Yang, Wei; Lin, Yangting
Abstract: The unusually prolonged volcanism at the Chang'e‐5 (CE‐5) landing site remains a mystery. To constrain the geochemical features of the CE‐5 mantle source, we performed in situ sulfur isotope analysis on sulfides of the CE‐5 basalts. The modal abundance of sulfides is ∼0.1 wt%, dominated by troilite with trace cubanite, chalcopyrite and pentlandite, yielding a S‐abundance of ∼360 ± 180 ppm for the bulk CE‐5 basalts. Our analysis shows a decreasing trend of δ 34 S in the magma with crystallization and degassing, suggesting ∼40% degassing loss of S, and accordingly the maximum S‐abundance in CE‐5 primitive magma was calibrated to approximately 600 ± 300 ppm. Considering an extensive fractional crystallization following a low‐degree partial melting of the CE‐5 basalts, the estimated sulfur abundance in the mantle source is ∼1–10 ppm. This result suggests a strong depletion of volatiles in the CE‐5 mantle source, which may be caused by prolonged magmatic activity. Plain Language Summary: The Chang'e‐5 (CE‐5) basalts are the youngest lunar samples identified so far, extending our knowledge of the duration of lunar volcanism, but the main factors of prolonging the volcanic activity are still unclear. Sulfur, with four stable isotopes ( 32 S, 33 S, 34 S, and 36 S) and an active component in magmatic activity, can constrain the magmatic processes and geochemical features of the mantle source. Here, we report the S isotope compositions of troilite in the CE‐5 samples. The sulfides are mainly troilite, with trace Cu‐ and Ni‐sulfides. We counted the modal abundance of sulfides and then obtained the S abundance of the bulk CE‐5 basalts. Analysis indicates that S isotope fractionation exists in the CE‐5 troilite and is mainly due to magma degassing. According to the variation in S isotope compositions, we corrected for the degassing loss of S and obtain the S abundance of the CE‐5 magma before eruption. Furthermore, we estimated the S abundance of the CE‐5 basalt source based on the formation of the CE‐5 magma. This estimated value is significantly lower than the estimations for Apollo basalt sources, implying multiple extractions of sulfur‐bearing melts from the CE‐5 mantle source due to its prolonged magmatic activity. Key Points: The δ 34 S values of troilite in the Chang'e‐5 basalts range from −1.6‰ to +2.0‰ The δ 34 S of troilite in the fine‐grained mesostasis are lighter than the inclusions in pyroxene, explained mainly by magma degassing It is expected that the mantle source of the Chang'e‐5 basalts is depleted in sulfur, which is ∼1–10 ppm with a δ 34 S of ∼0.5‰